Tuning the structural properties of CeO2 by Pr and Fe codoping for enhanced visible‐light catalytic activity. Issue 5 (27th February 2019) - Wen, Weijie; Lou, Zhencheng; Chen, Yanjin; Chen, Dingsheng; Tian, Shuanghong; Xiong, Ya
Abstract: BACKGROUND: Iron (Fe) 3+ has much a smaller ion radius than cerium (Ce) 4+ but praseodymium (Pr) ions have a similar radius to Ce ions with the same valence. Hence, it is interesting to tune the structural properties, including lattice deformation, band gap and oxygen vacancy (Ov ), of CeO2 by Pr and Fe codoping for enhanced visible‐light catalytic activity. RESULTS: A series of Ce1‐x‐y Prx Fey O2‐σ ( x  = 0∼0.012, y  = 0.003∼0.031) nanoparticles were prepared by a simple one‐step sol‐gel method. The structural properties of CeO2, including crystal deformation (cell lattice from 5.4069 to 5.4195), band gap (from 2.20 to 2.93), oxygen vacancies (Ov from 0.15% to 9.03%), and peroxide species (O2 2− from 0.37% to 1.09%) can be finely tuned by Pr and Fe codoping. Among ten samples, Ce0.982 Pr0.003 Fe0.015 O2‐σ with proper structural properties showed the highest photocatalytic activity towards the degradation of acid orange 7. The first reaction rate constant reaches 0.0687 min −1, 9.3 and 7.7 times that of Ce0.994 Pr0.006 O2‐σ and Ce0.985 Fe0.015 O2‐σ, respectively. The mechanism was found to involve ·OH, ·O2 − and photogenerated holes. CONCLUSION: The structural properties of CeO2 can be finely and easily tuned by Pr and Fe codoping. Thus, the photocatalytic activity of CeO2 under visible light irradiation was boosted. © 2019 Society of Chemical Industry